PENERAPAN TEORI DAN TEKNIK MODELING DALAM KONSELING ISLAM: KONSEP, TAHAPAN, DAN EFEKTIVITASNYA - Falihah Nuur Nafiah; Een Paniah; Farrel Hengkara Adi Putra; Naeila Rifatil Muna (Realita : Jurnal Bimbingan dan Konseling, 2026)
This study examines the concept, stages, and results of applying modeling techniques in Islamic counseling. Based on Bandura's Social Learning Theory, modeling emphasizes the learning process through observation and imitation of positive behaviors based on Islamic moral and spiritual values. Its implementation involves six stages: assessment, intervention planning, model selection, implementation, reinforcement, and evaluation. The results indicate that modeling is effective in improving adaptive behavior, emotional control skills, and the spiritual development of counselees. The concept of uswah hasanah, which combines moral and psychological training, aligns with this approach. Although its effectiveness depends on the quality of the model and the gradual internalization process, modeling remains an ethical and efficient method for developing holistic character in Islamic counseling.